2018
DOI: 10.1016/j.jnci.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapeutic factors affecting the incidence of developing hypothyroidism after radiotherapy for head and neck squamous cell cancer

Abstract: The V30 may predict risk of developing HT after RT for HNSCC patients. V30 of 42.1%, defined as dose-volumetric threshold of radiation-induced HT, can be useful in treatment planning of HNSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Also, the retrospective nature of some studies contributed to this variation. Using 3DCRT alone like our study and El-Sherbiney et al study [16] may contribute to different outcomes than using IMRT in other studies [2,14,15,28].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Also, the retrospective nature of some studies contributed to this variation. Using 3DCRT alone like our study and El-Sherbiney et al study [16] may contribute to different outcomes than using IMRT in other studies [2,14,15,28].…”
Section: Discussionmentioning
confidence: 54%
“…Our results have shown that the incidence of RIHT after maximum follow up of 24 months was 26%. The range of reported incidence from similar studies ranged from 17-47% [2,5,15,16,18,19]. Our follow up period is relatively short and the incidence is expected to increase with longer follow up periods.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations